GPs should actively ask about Symptoms of Urinary or Faecal Incontinence in Ageing Female Patients - Seppälä Tellervo; Ala-Nissilä Seija; Joronen Kirsi; Laasik Maren; Kauppila Marjo; Hautaniemi Soili; Rantanen Virpi (My University, 2026)
Objectives: To investigate how common incontinence problem is and how it could be detected in an unselected population.
Methods: Cross-sectional study in primary care population. A population survey of women born in 1948 or 1950 and living in a municipality with 19,535 inhabitants in south-western Finland in 2017. Main outcome measures were incidence of urinary or faecal incontinence.
Results: After analyzing the questionnaires and research findings, we found that urinary incontinence is a common phenomenon, reported by 50.3% of participants. According to the Urinary Incontinence Severity Score (UISS), 12.7% of them believed that the degree of disability was remarkable, and according to the Visual Analogue Scale (VAS), 18.3% considered the degree of disability to be difficult. In this study obesity was the most common feature affecting urinary incontinence.
Conclusion: Urinary incontinence is a common problem and will increase as the population ages. It can deteriorate a person’s quality of life, increase her need of care and involve considerable costs. Preventing the problem and treating it as early as possible in primary health-care is both reasonable and saves time and money.
Keywords: Conservative Treatment, Lifestyle, Medication, Quality of life, Urinary incontinence